Funk & Wagnalls modern guide to synonyms and related words : lists of antonyms, copious cross-references, a complete and legible index - Hayakawa, S. I. (Samuel Ichiyé), 1906- (Funk & Wagnalls, 1968)
In this comedy, Rowan Atkinson shows that there is comedy potential in every part of the body.